Efeitos de inibições inconscientes na aquisição da segunda língua - Fernandes, Otávia Pinheiro Pedrosa (2008)
The theme of this dissertation was chosen from questionings made by teachers of foreign languages: What makes that some people have so much difficulty in learning a foreign language? Why is there, almost always, in a class of at most 12 students, one that, even making greater effort, cannot keep up with the learning of their classmate? Pedagogy, teaching method, are they the only factors responsible for the acquisition of a second language? Would they be, then, the only factors to be questioned when there are difficulties in the learning of a second language? Investigating factors of the unconscious, as conceived by the theory of Freud and Lacan, would contribute with answers to the questions mentioned above? From these questions, so relevant for the teacher to be able to invest on the path that he will follow, aiming to get to understand how he can help his students, we decided to investigate, from the view of psychoanalysis and the analysis of the speech founded by Pêcheux, on students with difficulties in learning a foreign language, signs of unconscious inhibition. It is in the materiality of the language that other senses may be heard in the line of the speech of the subject, showing the linguistic mistake that causes the inhibition. From the analysis made, we can suggest that the french language is a symptom, taking place of significant. In a more specific way we will: a) analyze signs of inhibition in the speech of the student with learning difficulty; b) search for possible causes of the learning inhibition. For that, we have made non-directive interviews with five students, from a private school of the French language, aged between 20 and 46 years old, all with difficulty in learning French. The analysis of the data have been made in the perspective of the French school of analysis of the speech, mostly the third period, as well as of works of Freud and Lacan